The Influence of MYOB Accounting Software on the Performance of Company Financial Report - Emil Salim; Zefriyenni; Hanna Pratiwi; Fitri Yeni; Zerni Melmusi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Putra Indonesia YPTK, 2016)
In the last two decades, the necessity of information management and technology system has been proven as a very crucial need for many enterprises or companies. The use of computers in the office automation and integrated system is a must for companies to establish themselves in the business world. One of the basic management information systems that are crucial in the accounting program is the use of doing business transactions are considered able to simplify and streamline the fundamental needs for running a business, such as marketing and operations is also a financial statement of a company. This study aims to measure the extent of the influence of the use of accounting software on performance reporting on financial companies, one of which is using MYOB accounting software in assisting the settlement of financial reporting in a company.